Diagnostic usefulness of cone‐beam computed tomography versus multi‐detector computed tomography for sinonasal structure evaluation - Miran Han; Hyun Jun Kim; Jin Wook Choi; Do‐Yang Park; Jang Gyu Han (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Objective Cone‐beam computed tomography (CBCT) is a promising imaging modality for sinonasal evaluation, with advantages of relatively low radiation dose, low cost, and quick outpatient imaging. Our study aimed to compare the diagnostic performance and image quality of CBCT with those of multi‐detector computed tomography (MDCT) with different slice thickness. Methods We retrospectively reviewed 60 consecutive patients who had undergone both CBCT and MDCT. MDCT images was reconstructed with 1 and 3 mm slice thickness. The quantitative image quality parameters (image noise, signal‐to‐noise ratio [SNR], and contrast‐to noise ratio [CNR] were calculated and compared between the two imaging modalities. Two observers (ENT surgeon and neuroradiologist) evaluated the presence of seven sinonasal anatomic variations in each patient and interobserver agreements were analyzed. The diagnostic performance of CBCT (0.3 mm) and MDCT (3 mm) was assessed and compared with that of high resolution MDCT (1 mm), which is considered as the gold standard. Results The image noise was significantly higher and SNR and CNR values were lower in the CBCT (0.3 mm) group than in the MDCT groups (1 and 3 mm). The diagnostic performance of CBCT (0.3 mm) was similar to that of MDCT (1 mm) and superior to that of MDCT (3 mm). The highest interobserver agreement was for high resolution MDCT (1 mm), followed by CBCT (0.3 mm), and MDCT (3 mm). Conclusion Considering its low radiation dose, low cost, and ease of clinical access, CBCT may be a useful imaging modality for as first line sinonasal evaluation and repeated follow up. Study design: Retrospective study in a tertiary referral university center. Level of evidence: NA.